The Genogram in Helping Relationship - Abazi, Lejda (European Journal of Multidisciplinary Studies, 2016)
The Genogram is a graphical tool used by family therapists to systematize the chronologically and the composition of the family in question and parental relationships within it. The family therapist draws the genogram of the family and analyzing it as a team, draws on assumptions and dysfunctional aspects of strategic solutions that will then occur in session. The Genogram certainly draws from the idea of genealogical tree, but its attribution of authorship is clearly not shared. According to Anne A. Shutzenberger [1], for some it is traced back to Genososciogramma Henry Collomb, from genealogy (family tree) and Sociogram (representation of links and relationships), which he developed in Dakar and exhibited in Nice in 1978, starting from the reflections JL Moreno; for others it is traced back to Murray Bowen (referring to the conference on family therapy in 1967) and then to the conceptualization of the Group of Palo Alto [2] in California. In fact, for both processing paths of the genogram, distances seem shorter epistemological finding themselves in a ring of union in Frieda Fromm-Reichman, the first researcher who started filming family sessions with schizophrenic patients in 1948, and that in 1956 has worked with Moreno in Stanford [3] writing a book with him for four hands [4], with which the Group of Palo Alto [5], marking the birth of the Family Therapy. In truth, says still Shutzenberger, the genesis of Genogram seems to be rooted in the oldest soils, contains itself the concepts of "das Umbewusste" and "Collective Psyche" by S. Freud, and of "collective unconscious" of CG Jung.
Keywords: genogram, helping, relationship